The impact of logistics on economic cooperation in Central Asia - Hans-Christian Brauweiler; Aida Yerimpasheva; Assem Zakirova (OrdnungsPolitisches Portal (OPO), 2023)
The logistics sector is integrally connected to the growth of Central Asia's (CA) economies and the regional cooperation that underpins those economies. The research aims to demonstrate and justify the significance of the creation and execution of logistical initiatives and cooperative projects to expand economic cooperation in Central Asia. In this article, an exploratory design is used based on collecting secondary qualitative and quantitative data and analyzing selected cases of logistics routes, projects, and initiatives. The study is based on the positive and nominative approaches used in economics. Qualitative research in the form of an in-depth interview with the participants of the International Round Table "Regional Development in Central Asia: Approaches and Priorities" helped identify the main problems in developing logistics infrastructure in the Central Asian countries. Relationships between logistics performance, global competitiveness, and GDP were analyzed. The condition of the logistics and transportation networks in Central Asia is described by the World Bank's Logistics Performance Index (LPI). The growth of the logistics infrastructure influences the CA economies and fosters economic cooperation among Central Asian nations. Investing in logistics infrastructure generates employment opportunities and facilitates cross-border commerce in goods and services, which is crucial for economic cooperation. Likewise, Central Asia's logistics infrastructure and internal transport routes will never be able to compete with maritime transport. However, since the countries are at the crossroads of all routes in extensive Eurasia, they can discover their niche.
Keywords: 330; Economic Cooperation; Central Asia; Logistics; Logistics Performance Index (LPI); Regional Logistics Collaboration